Prevalence of progressive supranuclear palsy in Yonago: change throughout a decade. Issue 12 (11th October 2016) - Takigawa, Hiroshi; Kitayama, Michio; Wada‐Isoe, Kenji; Kowa, Hisanori; Nakashima, Kenji
Abstract: Background: Progressive supranuclear palsy (PSP) is a neurodegenerative disorder that is sometimes confused with Parkinson's disease, multiple system atrophy, and other disorders. The typical clinical features are categorized as Richardson's syndrome (RS), but other clinical subtypes include PSP‐parkinsonism (PSP‐P) and PSP‐pure akinesia with gait freezing (PSP‐PAGF). In this study, we determined the prevalence of PSP in a Japanese rural area compared to our previous 1999 report. Methods: We collected data in Yonago City from 2009 to 2014 using a service‐based study of PSP. We collected case history data from PSP patients in the area from our hospital. The crude prevalence and 95% confidence interval (CI) were calculated using the population demographics on the prevalence day of 1 October 2010. Age‐ and sex‐adjusted prevalence was calculated by direct standardization to the population demographics in Yonago City on the prevalence day of 1 April 1999. Material and Results: We identified 25 patients: 16 with probable RS, 4 with possible RS, 3 with clinical PSP‐P, and 2 with clinical PSP‐PAGF. The prevalence per 100, 000 was 17.90 (male = 18.05; female = 17.76). The prevalence of PSP in Yonago in 2010 increased compared to the measurements from 1999. Conclusion: The prevalence of PSP in Japan increased from 1999 to 2010. Abstract : The prevalence of progressive supranuclear palsy and Richardson's syndrome.